PELATIHAN PEMETAAN AKTIVITAS BISNIS MENGGUNAKAN BUSINESS MODEL CANVAS BAGI USAHA KECIL DAN MENENGAH KELURAHAN KEDUNG SARI KECAMATAN SUKA JADI KOTA PEKANBARU - Arafat A., Lathif; Meta, Williya; Meilisa, Meilisa (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2024)
This service aims to improve the competitiveness of Small and Medium Enterprises (SMEs) in Kedung Sari Village, Sukajadi District, Pekanbaru City, through Business Model Canvas (BMC) training. The programme involved 35 participants from various sectors, who were given intensive training and mentoring on the nine components of BMC, such as customer segments, value proposition, and revenue streams. The methods used included initial coordination, theoretical training, and practical mentoring sessions on BMC development. Evaluation results showed that participants' understanding of the BMC improved in designing a more structured business model and a more effective strategy, although some still needed support for consistent implementation. The training had a positive impact on the development of local SMEs and recommends a more in-depth follow-up programme in the application of digital marketing strategies and business mapping to ensure the sustainability of improved business competitiveness.